Sustainable Tourism Post-Pandemic: A Mini-Review of Best Practices for "New Normal" Destinations in Bali - Anneke W, Jeanny Pricilia; Khan, Jamil; Zaman, Khalil (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. The COVID-19 pandemic has had a profound impact on the global tourism industry, particularly in popular destinations like Bali, Indonesia. As the world begins to recover, tourism faces the challenge of adapting to a "new normal" that prioritizes sustainability, health protocols, and local community involvement. This mini-review explores best practices for sustainable tourism in Bali, focusing on how destinations can adapt post-pandemic while ensuring long-term environmental, social, and economic benefits. Purpose. The primary aim of this study is to assess the sustainability strategies implemented by Bali's tourism sector in the aftermath of the pandemic.   Method. A qualitative review was conducted, examining existing literature, government reports, and case studies of sustainable tourism practices in Bali. The review identifies key areas such as eco-tourism, community-based tourism, and the integration of health and safety standards into tourism operations. Results. The findings highlight that Bali has begun to implement a range of sustainable practices, including the promotion of eco-friendly accommodations, the development of responsible tourism guidelines, and the involvement of local communities in decision-making. However, challenges such as over-tourism, waste management, and the need for further collaboration among stakeholders remain. Conclusion. In conclusion, Bali’s tourism sector is taking positive steps toward sustainability post-pandemic, but continued efforts are required to ensure resilience and long-term success. Further research and investment in sustainable tourism infrastructure, coupled with local and global cooperation, will be crucial to the future of Bali as a "new normal" destination.